Ethylene response factor SlERF.D6 promotes ripening in part through transcription factors SlDEAR2 and SlTCP12 - Yao Chen; Xin Wang; Vincent Colantonio; Zhuo Gao; Yangang Pei; Tara Fish; Jie Ye; Lance Courtney; Theodore W. Thannhauser; Zhibiao Ye; Yongsheng Liu; Zhangjun Fei; et al. (Proceedings of the National Academy of Sciences, 2025)
Ripening is crucial for the development of fleshy fruits that release their seeds following consumption by frugivores and are important contributors to human health and nutritional security. Many genetic ripening regulators have been identified, especially in the model system tomato, yet more remain to be discovered and integrated into comprehensive regulatory models. Most tomato ripening genes have been studied in pericarp tissue, though recent evidence indicates that locule tissue is a site of early ripening-gene activities. Here, we identified and functionally characterized an Ethylene Response Factor (ERF) gene, SlERF.D6 , by investigating tomato transcriptome data throughout plant development, emphasizing genes elevated in the locule during fruit development and ripening. SlERF.D6 loss-of-function mutants resulting from CRISPR/Cas9 gene editing delayed ripening initiation and carotenoid accumulation in both pericarp and locule tissues. Transcriptome analysis of lines altered in SlERF.D6 expression revealed multiple classes of altered genes including ripening regulators, in addition to carotenoid, cell wall, and ethylene pathway genes, suggesting comprehensive ripening control. Distinct regulatory patterns in pericarp versus locule tissues were observed, indicating tissue-specific activity of this transcription factor (TF). Analysis of SlERF.D6 interaction with target promoters revealed an APETALA 2/ETHYLENE RESPONSE FACTOR (AP2/ERF) TF ( SlDEAR2 ) as a target of SlERF.D6. Furthermore, we show that a third TF gene, SlTCP12 , is a target of SlDEAR2, presenting a tricomponent module of ripening control residing in the larger SlERF.D6 regulatory network.